71 QR code, document studio and patient safety. (3rd November 2019) - Irfan, Mohammad; Mutairi, Najla Al; Bhutta, Muna
Abstract : Aims: Think Out Of Box To know about application of technology(google add on) in Incident Reporting to overcome barriers, such as, Complex system of reporting, time consuming, manpower and supplies issues, feedback issues, fear of punitive action, and inability to report as anonymous. Methods: Google add ons like spredsheet, document studio and QR code was designed and used for incident reporting, getting responses and giving feedbacks. Results: Incident reporting was increased to nearly 3 to 4 times. Incident reporting barriers were removed. Monitoring of the compliance to the essential safety standards(Blood transfusion reaction, Patient identification, Safe and correct procedure, venous thromboembolism prophylaxis) was made easy. Even Patients started to contribute in Incident reporting. Conclusion: With the help of the applied google tools, we were able to have a direct live access to the dashboard for Incident reporting and also helped to monitor Indicators of patient safety, particularly, the timeliness of the OVR(Occurance Variance Report) System.